Impact of Frailty on Mortality and Hospitalization in Chronic Heart Failure: A Systematic Review and Meta‐Analysis. Issue 23 (4th December 2018) - Yang, Xiaobo; Lupón, Josep; Vidán, Maria T.; Ferguson, Caleb; Gastelurrutia, Paloma; Newton, Phillip J.; Macdonald, Peter S.; Bueno, Héctor; Bayés‐Genís, Antoni; Woo, Jean; Fung, Erik
Abstract : Background: Although frailty has been associated with increased risks for hospitalization and mortality in chronic heart failure, the precise average effect remains uncertain. We performed a systematic review and meta‐analysis to summarize the hazards for mortality and incident hospitalization in patients with heart failure and frailty compared with those without frailty and explored the heterogeneity underlying the effect size estimates. Methods and Results: MEDLINE, EMBASE, and Cochrane databases were queried for articles published between January 1966 and March 2018. Predefined selection criteria were used. Hazard ratios (HRs) were pooled for meta‐analyses, and where odds ratios were used previously, original data were recalculated for HR. Overlapping data were consolidated, and only unique data points were used. Study quality and bias were assessed. Eight studies were included for mortality (2645 patients), and 6 studies were included for incident hospitalization (2541 patients) during a median follow‐up of 1.82 and 1.12 years, respectively. Frailty was significantly associated with an increased hazard for mortality (HR, 1.54; 95% confidence interval, 1.34–1.75; P <0.001) and incident hospitalization (HR, 1.56; 95% confidence interval, 1.36–1.78; P <0.001) in chronic heart failure. The Fried phenotype estimated a 16.9% larger effect size than the combined Fried/non‐Fried frailty assessment for the end point of mortality (HR, 1.80; 95% confidence interval, 1.41–2.28; P <0.001), but not for hospitalization (HR, 1.57; 95% confidence interval, 1.30–1.89; P <0.001). Study heterogeneity was found to be low (I 2 =0%), and high quality of studies was verified by the Newcastle‐Ottawa scale. Conclusions: Overall, the presence of frailty in chronic heart failure is associated with an increased hazard for death and hospitalization by ≈1.5‐fold.